Seawater carbonate chemistry and the mechanisms behind swimming performance of Atlantic king scallop - Christian Bock; Sandra Götze; Hans-Otto Pörtner; Gisela Lannig (PANGAEA, 2025)
In the present study we therefore used a semitargeted, multi tissue NMR based metabolomic approach to analyze metabolite patterns in the Atlantic king scallop, Pecten maximus, that were long-term acclimated to different end of century conditions of ocean warming (OW), ocean acidification (OA) and their combination (OWA). We investigated tissue specific metabolic profiles and metabolite concentrations in frozen tissues from gills, mantle and phasic and tonic adductor muscle of P. maximus under present conditions using 1H-HR-MAS NMR spectroscopy. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2015) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI).